Effect of aspiration on the lungs in children: a comparison using chest computed tomography findings - Nobukazu Tanaka; Kanji Nohara; Akihito Ueda; Tamami Katayama; Miyuki Ushio; Nami Fujii; Takayoshi Sakai (BMC, 2019)
Abstract Background Detecting and addressing aspiration early in children with dysphagia, such as those with cerebral palsy, is important for preventing aspiration pneumonia. The current gold standards for assessing aspiration are swallowing function tests, such as fiberoptic endoscopic evaluation of swallowing (FEES) and videofluorographic swallowing study; however, the relationship between aspiration of secretion vs aspiration of foodstuff and pulmonary injury is unclear. To clarify this relationship, we examined the correlations between pneumonia findings from chest computed tomography (CT) and the presence or absence of aspiration detected by FEES. Methods Eighty-five children (11 years 2 months ±7 years 2 months) underwent FEES and chest CT. Based on the FEES findings, the participants were divided into groups: with and without food aspiration, and with and without saliva aspiration. Correlations between chest CT findings of pneumonia and the presence or absence of each type of aspiration were then examined. Results No significant correlations were observed between food aspiration and chest CT findings of pneumonia, whereas saliva aspiration and chest CT findings of pneumonia were significantly correlated. In addition, saliva aspiration was significantly associated with bronchial wall thickening (p < 0.01) and atelectasis (p < 0.05). Conclusions Our findings in children suggest that: (1) the presence or absence of food aspiration detected by FEES evaluation has little correlation with pneumonia, and (2) the presence or absence of saliva aspiration may be an indicator of aspiration pneumonia risk.